SBRC-Nottingham: Sustainable Routes to Platform Chemicals from C1 Wastes Gases - Minton, Nigel P.; Burbidge, Alan (Portland Press Ltd, 2016)
SBRC-Nottingham (www.sbrc-nottingham.ac.uk) was one of the first three UK university-based Synthetic Biology Research Centres (SBRCs) to be funded by the BBSRC and EPSRC as part of the recommendations made in the UKs Synthetic Biology Roadmap. It was established in 2014 and builds on the pioneering work of the Clostridia Research Group (CRG) who have previously developed a range of gene tools for the modification of clostridial genomes [1-9].